Dlx1/2 mice have abnormal enteric nervous system function - Christina M. Wright; James P. Garifallou; Sabine Schneider; Heather L. Mentch; Deepika R. Kothakapa; Beth A. Maguire; Robert O. Heuckeroth (JCI Insight, 2020)
Decades ago, investigators reported that mice lacking DLX1 and DLX2, transcription factors expressed in the enteric nervous system (ENS), die with possible bowel motility problems. These problems were never fully elucidated. We found that mice lacking DLX1 and DLX2 (Dlx1/2–/– mice) had slower small bowel transit and reduced or absent neurally mediated contraction complexes. In contrast, small bowel motility seemed normal in adult mice lacking DLX1 (Dlx1–/–). Even with detailed anatomic studies, we found no defects in ENS precursor migration, or neuronal and glial density in Dlx1/2–/– or Dlx1–/– mice. However, RNA sequencing of Dlx1/2–/– ENS revealed dysregulation of many genes, including vasoactive intestinal peptide (Vip). Using immunohistochemistry and reporter mice, we then found that Dlx1/2–/– mice have reduced VIP expression and fewer VIP-lineage neurons in their ENS. Our study reveals what we believe is a novel connection between Dlx genes and Vip and highlights the observation that dangerous bowel motility problems can occur in the absence of easily identifiable ENS structural defects. These findings may be relevant for disorders like chronic intestinal pseudo-obstruction (CIPO) syndrome.